+0  
 
+1
237
2
avatar+322 

How to simplify the equation -3sqrt(5)/sqrt(15)

Davis  Mar 2, 2017

Best Answer 

 #1
avatar+7155 
+6

\(\frac{-3\sqrt{5}}{\sqrt{15}} \\ = \frac{-3\sqrt{5}(\sqrt{15})}{\sqrt{15}(\sqrt{15})} \\ = \frac{-3\sqrt{75}}{15} \\ = \frac{-3(5\sqrt{3})}{15} \\ = \frac{-15\sqrt{3}}{15} \\ = -\sqrt{3}\)

 

:)

hectictar  Mar 2, 2017
 #1
avatar+7155 
+6
Best Answer

\(\frac{-3\sqrt{5}}{\sqrt{15}} \\ = \frac{-3\sqrt{5}(\sqrt{15})}{\sqrt{15}(\sqrt{15})} \\ = \frac{-3\sqrt{75}}{15} \\ = \frac{-3(5\sqrt{3})}{15} \\ = \frac{-15\sqrt{3}}{15} \\ = -\sqrt{3}\)

 

:)

hectictar  Mar 2, 2017
 #2
avatar+322 
+5

Thx

Davis  Mar 2, 2017

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.